War Is Ugly: A Critical Appraisal Of The Consequences Of The Nigerian Civil War In Flora Nwapas Never Again And Chimamanda Adichies Half Of A Yellow Sun - Onyeka Ike (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
The Nigerian Civil War having being heralded by certain avoidable dark clouds which a capriciousl leadership in power at the time failed to mollify eventually resulted to certain catastrophic and mind-boggling consequences. Indeed, no progressive nation would desire to see a repetition of such ugly, cruel and inhuman occurrences. Both individual and community experiences as portrayed in Nwapas Never Again and Adichies Half of a Yellow Sun point to the fact that the sufferings, deaths and anguish occasioned by the war were really enormous and unbearable. Using New Historicism as a critical model, investigations as guided by the two aforementioned war fictions reveal that invaluable talents and potentials were flagrantly wasted, peace a paramount precursor of development gave way to pieces, women and girls were horribly abused and debased in the most animalistic manner, and vital infrastructures were destroyed. Yet the war did not achieve any of the goals for which it broke out - Biafra did not secede; Nigeria is still far from being united as one country still a mere coalition of ethnic nationalities held together by the Van der Waals forces of federation account and revenue allocation. Moreover, the dark clouds that resulted to the war are still largely palpable and unaddressed. The paper also explores the consideration of peaceful negotiation and dialogue as a better alternative to conflict resolution rather than bloodshed.